Raw hulled shredded acorns from Downy Oak (Quercus pubescens) in the diet of pigs: effects on digestibility and faeces characteristics. Issue 1 (2nd May 2013) - Cappai, M. G.; Wolf, P.; Rust, P.; Pinna, W.; Kamphues, J.
Summary: Faeces quality and composition are both of interest to veterinary practitioners dealing with pigs' health and disturbances in the alimentary tract, especially in free‐range situations. In the Mediterranean basin, acorns are used as a starch source for fattening pigs, yet little information is available on how that affects faecal quality and digestibility. Therefore, a combined diet containing ripe hulled shredded acorns vs. a pelleted complete diet for finishers was evaluated for the digestibility and faecal consistency. The trial involved eight crossbred pigs, and a matched‐pair approach was used to divide animals into two groups, which were fed with two different diets: acorns group (A): n = 4, 70% ripe hulled shredded acorns + 30% pelleted complete diet combined, as fed; control group (C): n = 4, 100% pelleted complete feed. The pigs were housed individually and fed the experimental diets for 8 days; daily feed intake and faeces amounts were recorded and faeces quality assessed. The digestibility of organic matter (OM) and starch of the two diets, as well as of pure acorns, were calculated and compared. Daily feed consumption was significantly higher in group A, but the mean dry matter intake (DMI) per pig was similar in both groups. Dark, firm and consistent faeces were reported for each pig from group A in comparison with group B, whose faeces were paler and softer. Digestibility of OM and starch were lower in group A than in group B (67.8 ± 3.4 vs. 83.9 ± 1.1 and 82.5 ± 3.4 vs. 92.3 ± 2.1 respectively): total tract digestibility of native starch from pure acorns was calculated at 77%. The peculiar consistency of faeces was related to macroscopic acorn hulls, constantly detected in the faeces of all animals sampled in group A.